Effectiveness of alternative investment towards financing environment: the adoption of present rules in terms of entrepreneur, venture capital firms and investors perspectives - Rawshon, Shahriar (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2016.